Abortos En Equinos Por Causas Bacterianas En Colombia Y A Nivel General (2024)
Equine abortion, especially when caused by bacterial infections, represents a significant problem for the equine industry in Colombia and worldwide, with substantial economic and animal health implications. The objective was to analyze the bacterial causes of abortions in mares, providing a comprehensive understanding of their etiology, diagnosis, prevention, and management, both in the Colombian and international context.